Métodos de labranza en las características agronómicas de Brassica napus L. Nabo var. Minowase. Loreto 2023 - Del Aguila Sandoval, Luis Jerson (2024)
Tillage are activities that, over time, form the ideal soil in order to ideal soil in order to allow the root system to explore the largest volume of soil and to to explore the largest volume of soil and absorb the available nutrients. The objective of this study was to evaluate the effect of tillage types on agronomic tillage types on the agronomic characteristics and yield of Brassica napus L. Nabo var. Minowase. Loreto 2023. The study was conducted at the Faculty of Agronomy-UNAP, Horticultural Plants Workshop. A completely randomized block design was used (DBCA) with 2 treatments (T0: manual tillage and T1: mechanical tillage). and T1: mechanized tillage) with 12 replications. The main conclusions were that the main conclusions were that the agronomic characteristic of plant extension did show significant differences significant differences between soil tillage types., which meant a greater leaf area to capture more solar energy and accumulation of reserves, the root diameter and length characteristics did present significant differences between soil tillage types, but contrary, since the diameter was greater and lesser in length in manual tillage, respectively, and in mechanized tillage the diameter was lesser and greater in length, respectively, the aerial part (leaf weight) was lesser in manual tillage (50. 64 g) than in mechanized tillage (61.67 g), root weight, actual and potential yield showed the highest results with manual tillage (142.2 g, 24,923 kg ha-1 and 35,604 kg ha-1), mechanized tillage is not always synonymous with crop yield.